Balancing marine environmental protection and global trade: regulating maritime sector in Malaysia - Mustafa, Maizatun; Hamid, Abdul Ghafur@Khin Maung Sein; Rusli, Mohd Hazmi (Journal of Contemporary Management Sciences, 2014)
It is acknowledged that maritime sector is the backbone of international trade with around 80 percent global trade is carried by sea. Similar to many other maritime nations, Malaysia is relying on the growth of its maritime sector to facilitate its global trade and related activities. However, in the overall context of sustainable development, the main concern for Malaysia and elsewhere is relating to the impact of the maritime sector on the environment. If left unregulated, any unsustainable practices are likely to intensify, increasing the potential for global environmental issue, and undermining progress being made on sustainable development. Reflecting this new reality, Malaysia must ensure that the growth of its maritime sector takes into account environmental consideration. This article is about steps taken by Malaysia to balance marine environmental protection and global trade by means of enhancing its maritime sector’s environmentally sustainable practices . This article looks at the existing domestic and international environmental law relevant to maritime sector, examines issues concerning the implementation of these laws, and suggests the way forward. Significantly, such effort can be used as reference and comparison by other maritime nations to develop relevant policies and measures especially for developing countries.